Bioptic Study of Left and Right Atrial Interstitium in Cardiac Patients with and without Atrial Fibrillation: Interatrial but Not Rhythm-Based Differences - Smorodinova, Natalia; Lantová, Lucie; Bláha, Martin; Melenovský, Vojtěch; Hanzelka, Jan; Pirk, Jan; Kautzner, Josef; Kučera, Tomáš (PloS one, 2015)
One of the generally recognized factors contributing to the initiation and maintenance of atrial fibrillation (AF) is structural remodeling of the myocardium that affects both atrial cardiomyocytes as well as interstitium. The goal of this study was to characterize morphologically and functionally interstitium of atria in patients with AF or in sinus rhythm (SR) who were indicated to heart surgery. Patient population consisted of 46 subjects (19 with long-term persistent AF, and 27 in SR) undergoing coronary bypass or valve surgery. Peroperative bioptic samples of the left and the right atria were examined using immunohistochemistry to visualize and quantify collagen I, collagen III, elastin, desmin, smooth muscle actin, endothelium and Vascular Endothelial Growth Factor (VEGF). The content of interstitial elastin, collagen I, and collagen III in atrial tissue was similar in AF and SR groups. However, the right atrium was more than twofold more abundant in elastin as compared with the left atrium and similar difference was found for collagen I and III. The right atrium showed also higher VEGF expression and lower microvascular density as compared to the left atrium. No significant changes in atrial extracellular matrix fiber content, microvascular density and angiogenic signaling, attributable to AF, were found in this cohort of patients with structural heart disease. This finding suggests that interstitial fibrosis and other morphological changes in atrial tissue are rather linked to structural heart disease than to AF per se. Significant regional differences in interstitial structure between right and left atrium is a novel observation that deserves further investigation.
Keywords: Collagen Type I; srdce - funkce síní; Heart Atria; Collagen Type III; Male; kolagen typu I; Organ Specificity; Heart Rate; Atrial Function; Aged; Case-Control Studies; mužské pohlaví; senioři; srdeční frekvence; extracelulární matrix; srdeční síně; kolagen typ III; Atrial Fibrillation; Elastin; lidé; ženské pohlaví; studie případů a kontrol; Humans; Extracellular Matrix; orgánová specificita; elastin; Female; lidé středního věku; fibrilace síní; Middle Aged